Non-absorbable running suture in coarctation repair in infants: a cross-sectional study - Opas Satdhabudha; Manita Songvasin; Utairat Chaumrattanakul; Charinee Kantasiripitak (Journal of Cardiothoracic Surgery)
Abstract Background In our institute, resection and aortic anastomosis for newborns and infants with coarctation of the aorta are typically performed using continuous nonabsorbable (polypropylene) sutures. This cross-sectional survey aims to examine the anastomosis site, focusing on the prevalence of growth and its correlation with recoarctation in cases requiring surgical reintervention. Methods Patients who underwent aortic anastomosis for symptomatic coarctation during their first year of life between 2008 and 2023 and were still alive were included in the study for evaluation. Aortic arch diameters were assessed using computed tomography angiography (CTA), and z-scores were calculated. For patients with recurrent stenosis who required subsequent surgery, the surgical pathology was reviewed. Results A total of 15 patients underwent CTA assessment, with a median time from surgery to CTA of 8.08 years (4.39, 10.02). The z-scores for the diameters at the repaired areas were as follows: for the distal transverse arch, the median z-score was − 0.08 (-0.52, 0.59), and for the descending aorta at the anastomosis, it was 1.13 (0.18, 1.72). When comparing the two subgroups—7 patients with aortic arch hypoplasia and 8 without—no significant differences were found in the z-scores of the diameters at the repaired sites. In one case of restenosis at the 4-year follow-up, subsequent surgery revealed that the suture line did not align with the narrowest segment. Conclusions Using continuous non-absorbable suture for aortic anastomosis in coarctation repair for newborns and infants can result in the growth of the aortic arch and the anastomosis site reaching the normal range, regardless of the presence of aortic arch hypoplasia. Pathological findings from a surgical reintervention indicate that the aortic wall segment containing suture material does not align with the area exhibiting the greatest narrowing. Trial registration Trial registration number (Study ID): TCTR20240412007.